2020
DOI: 10.22137/ijst.2020.v4n1.05
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening of Fish Poison Tree, Barringtonia Asiatica Seed for Potential Biopesticidal Activity and Pharmaceutical Uses

Abstract: The leaves are locally used as vegetable food, herb, spice, and medication for backaches, sore joints, rheumatism, hernia, and diarrhea (Barwick, 2004). According to Stuart (2018), in the Philippines, leaves are heated and applied as topical remedy for stomachache. Similarly, Ravikumar et al. (2015) reported that the Nicobari tribe of India utilized leaves for the treatment of fractures, wounds, de-worming, and pain relief. The flowers are large pinkish-white, which give off a sickly-sweet smell to attract bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The presence of numerous secondary metabolites found in B. asiatica, such as alkaloids, flavonoids, and glycosides, among others, have been previously reported in seed extracts. The efficacy of saponins, also present in the seed, against cancer cells has been attributed to their ability to inhibit cell proliferation, stimulate apoptosis, and reduce angiogenesis [64]. Therefore, these compounds plausibly account for the cytotoxic activity of B. asiatica seed extract against ovarian carcinoma (A2780) cell line in this study.…”
Section: Cell Viability Of Ovarian Carcinoma (A2789) (Live/dead Fluorescence Assay)mentioning
confidence: 76%
“…The presence of numerous secondary metabolites found in B. asiatica, such as alkaloids, flavonoids, and glycosides, among others, have been previously reported in seed extracts. The efficacy of saponins, also present in the seed, against cancer cells has been attributed to their ability to inhibit cell proliferation, stimulate apoptosis, and reduce angiogenesis [64]. Therefore, these compounds plausibly account for the cytotoxic activity of B. asiatica seed extract against ovarian carcinoma (A2780) cell line in this study.…”
Section: Cell Viability Of Ovarian Carcinoma (A2789) (Live/dead Fluorescence Assay)mentioning
confidence: 76%
“…These compounds, in particular polyphenol, give the antioxidant property. Another reported that the seed of Barringtonia asiatica L. (Kurz) generally has a higher diversity of secondary metabolites such as saponin, terpenoid, tannin, flavonoid, coumarine, cardiac glycoside and alkaloid [12]. Although the study of phytochemical analysis of Barringtonia asiatica L. (Kurz) is already established quiet well, but the same study from different geographical area is important to elucidate its potential locally.…”
Section: Introductionmentioning
confidence: 99%